Participatory Governance of Customary Forests: Institutional Collaboration in Islamic Law and Customary Law Perspectives - Rusmiyati, Chatarina; Wahyono, Eko; Carolina, Carolina; Tursilarini, Tateki Yoga; Tantri, Erlita (Al-Manahij: Jurnal Kajian Hukum Islam, 2026)
This study analysis institutional collaboration between customary and religious systems in customary forest management through the lens of participatory and sustainable social ecological governance, emphasizing Islamic environmental jurisprudence (fiqh al-bī’ah). It challenges state-centric and top-down forest governance models by highlighting locally embedded regulatory frameworks that integrate customary norms with Islamic legal-ethical principles derived from uṣūl al-fiqh and maqāṣid al-sharī‘ah. The study asks how interactions between customary institutions and religious authorities function as socially legitimate mechanisms that sustain ecological balance while improving indigenous welfare. Using a mixed-methods design, the research combines quantitative analysis through Structural Equation Modeling–Partial Least Squares (SEM-PLS) with qualitative inquiry including in-depth interviews and focus group discussions with customary leaders, religious authorities, and community members. Results show that integrating customary law and Islamic jurisprudence generates strong social legitimacy grounded in khilāfah, amānah, and maṣlaḥah. Religious moral sanctions and environmental ethical narratives reinforce compliance with customary ecological norms and strengthen collective participation. The study concludes that adat religious collaboration represents a normative governance model aligned with maqāṣid al-sharī‘ah, particularly the protection of life, resources, and ecological balance. This model offers a jurisprudential foundation for inclusive and participatory forest governance that respects legal pluralism while supporting indigenous welfare and environmental sustainability.